Transcriptional Dynamics Driving MAMP-Triggered Immunity and Pathogen Effector-Mediated Immunosuppression in Arabidopsis Leaves Following Infection with Pseudomonas syringae pv tomato DC3000. Issue 11 (13th November 2015) - Lewis, Laura A.; Polanski, Krzysztof; de Torres-Zabala, Marta; Jayaraman, Siddharth; Bowden, Laura; Moore, Jonathan; Penfold, Christopher A.; Jenkins, Dafyd J.; Hill, Claire; Baxter, Laura; Kulasekaran, Satish; Truman, William; et al.
Abstract : High-resolution microarray analysis of Pseudomonas   syringae -inoculated Arabidopsis leaves reveals transcriptional dynamics underpinning basal defense and effector modulation leading to disease development. Abstract: Transcriptional reprogramming is integral to effective plant defense. Pathogen effectors act transcriptionally and posttranscriptionally to suppress defense responses. A major challenge to understanding disease and defense responses is discriminating between transcriptional reprogramming associated with microbial-associated molecular pattern (MAMP )-triggered immunity (MTI ) and that orchestrated by effectors. A high-resolution time course of genome-wide expression changes following challenge with Pseudomonas syringae pv tomato DC3000 and the nonpathogenic mutant strain DC3000 hrpA- allowed us to establish causal links between the activities of pathogen effectors and suppression of MTI and infer with high confidence a range of processes specifically targeted by effectors. Analysis of this information-rich data set with a range of computational tools provided insights into the earliest transcriptional events triggered by effector delivery, regulatory mechanisms recruited, and biological processes targeted. We show that the majority of genes contributing to disease or defense are induced within 6 h postinfection, significantly before pathogen multiplication. Suppression of chloroplast-associated genes is a rapid MAMP -triggered defense response, and suppression of genes involved in chromatin assembly and induction of ubiquitin-related genes coincide with pathogen-induced abscisic acid accumulation. Specific combinations of promoter motifs are engaged in fine-tuning the MTI response and active transcriptional suppression at specific promoter configurations by P. syringae .